Шифрування WI-FI 6-мереж - Фодченко, А. В. (ХНУРЕ, 2024)
The purpose of this article is to look at and analyze the main aspects of encryption in Wi-Fi 6 in order to understand its importance, effectiveness and impact on the security and privacy of data. The report aims to present the technical details of encryption, including the developed cryptographic algorithms and protocols, as well as evaluate its effectiveness against a variety of threats and attacks. In addition, the evidence can include continuous analysis of the latest versions of Wi-Fi protocols, highlighting the advantages and disadvantages of the new approach to encrypting Wi-Fi data.
Keywords: шифрування; WI-FI 6-мережа